2013
DOI: 10.1002/jsfa.6179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vegetarian diets on zinc status: a systematic review and meta‐analysis of studies in humans

Abstract: Plant-based diets contain less saturated fat and cholesterol and more folate, fibre and phytochemicals than omnivorous diets, but some micronutrients, especially zinc, are poorly bioavailable. The findings of studies exploring the zinc intake and zinc status in populations that habitually consume vegetarian diets are inconsistent. This study aims to investigate the effects of plant-based diets on dietary zinc intake and status in humans using systematic review and meta-analysis techniques. Thirty-four studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 110 publications
2
43
0
3
Order By: Relevance
“…Plasma zinc levels were lower in these women than in non-pregnant women, suggesting that zinc nutritional status is influenced more by pregnancy than by LOV/ OMN diet [191]. Nevertheless those on a VEG diet have lower zinc intake [192] and lower zinc plasma levels [101] than those on a LOV diet.…”
Section: Nutritional Status Of Vegetarians At Different Agesmentioning
confidence: 79%
“…Plasma zinc levels were lower in these women than in non-pregnant women, suggesting that zinc nutritional status is influenced more by pregnancy than by LOV/ OMN diet [191]. Nevertheless those on a VEG diet have lower zinc intake [192] and lower zinc plasma levels [101] than those on a LOV diet.…”
Section: Nutritional Status Of Vegetarians At Different Agesmentioning
confidence: 79%
“…Given this disparity, it is unsurprising that a recent meta-analysis found zinc intakes and zinc status to be lower among males and females following a vegetarian diet compared to those who consume meat [21]. The iron content of the foods in Figure 1 are more comparable, with animal-derived foods containing 0.64% less iron than unfortified plant-derived foods (mean 3.0 mg vs. 3.1 mg).…”
Section: Dietary Sources and Intakes Of Iron And Zincmentioning
confidence: 99%
“…We investigated the effects of plant-based diets on zinc status and showed that dietary zinc intakes and serum zinc concentrations were significantly lower in populations that followed habitual vegetarian diets compared to non-vegetarians. Secondary analyses revealed greater impact of vegetarian diets on the zinc status of females, vegetarians from low-and middle-income countries (LMIC), and vegans [8,9]. Although not all vegetarian diets impact zinc status to the same extent, populations that habitually consume vegetarian diets with high PA:Zn molar ratios have a requirement for dietary zinc that is substantially greater than the amount recommended for omnivores.…”
Section: Plant-based Diets and Zinc Statusmentioning
confidence: 98%